2008
DOI: 10.1007/s10334-008-0158-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring kidney and renal cyst volumes applying MR approaches on a rapamycin treated mouse model of ADPKD

Abstract: Using MRI, we were able to monitor the cystic volume in a mouse model of PKD to assess the therapeutic effect of anticystic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 23 publications
(42 reference statements)
2
30
0
Order By: Relevance
“…These studies demonstrated that kidney volume can be quantified in an unbiased fashion with minimum intra- and inter-observer variabilities. However, because of the use of CM, most of these studies did not include patients with CKD [3,9,11,16]. Moreover, gadolinium even seems to modify the TRV measurement in ADPKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies demonstrated that kidney volume can be quantified in an unbiased fashion with minimum intra- and inter-observer variabilities. However, because of the use of CM, most of these studies did not include patients with CKD [3,9,11,16]. Moreover, gadolinium even seems to modify the TRV measurement in ADPKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, [2,3,7,8,9,10,11,12,14,15,16] several authors described methods for TRV assessment in ADPKD patients based on the analysis of data acquired using iodinated CM or gadolinium. These studies demonstrated that kidney volume can be quantified in an unbiased fashion with minimum intra- and inter-observer variabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the potential of using MRI to monitor the development of kidney cysts in animal models of cystic diseases (Reichardt et al, 2009). The surrounding parenchyma and cysts can be clearly distinguished by the differences in signal intensities between parenchyma Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging of mouse kidneys has been performed in vivo primarily with X-ray micro-CT [2] and MRI [3,4,5]. Typically, the analysis of the images has been performed with extensive manual annotation [4,5].…”
Section: Introductionmentioning
confidence: 99%